2019
DOI: 10.1002/cssc.201902697
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Conjugated Polycatechol Organic Cathode for Aqueous Zinc‐Ion Storage

Abstract: Supporting Information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 48 publications
0
68
0
Order By: Relevance
“…Interestingly, its red shi in the Li + (1202 cm À1 ) < Zn 2+ (1106 cm À1 ) < Al 3+ (1029 cm À1 ) order indicates stronger interaction of M n+ with C-O À in the same order of metal cation valences. 40,51 Taken together, these results conrm that the cations of the supporting electrolytes are mainly involved in the electrochemical reaction. However, despite all those control experiments, we cannot completely exclude the involvement of protons on the redox mechanism in acidic electrolytes and further studies would be necessary to undoubtedly elucidate this aspect.…”
Section: Effect Of Charge Carriers On the Electrochemical Responsementioning
confidence: 70%
See 2 more Smart Citations
“…Interestingly, its red shi in the Li + (1202 cm À1 ) < Zn 2+ (1106 cm À1 ) < Al 3+ (1029 cm À1 ) order indicates stronger interaction of M n+ with C-O À in the same order of metal cation valences. 40,51 Taken together, these results conrm that the cations of the supporting electrolytes are mainly involved in the electrochemical reaction. However, despite all those control experiments, we cannot completely exclude the involvement of protons on the redox mechanism in acidic electrolytes and further studies would be necessary to undoubtedly elucidate this aspect.…”
Section: Effect Of Charge Carriers On the Electrochemical Responsementioning
confidence: 70%
“…Additionally, this redox reaction mechanism with the coordination/uncoordination of designated metal cations has been also well proven for both PC and PI elsewhere in the context of metal-ion aqueous batteries. [34][35][36][37][38][39][40] The reduction of ortho-quinones into catecholates and the subsequent n-type coordination reaction depend not only on the pH of the aqueous electrolyte, but also on the nature and concentration of cationic charge carriers. 49 As control experiments, we accomplished CV analysis of PC in both aqueous citrate buffer solutions (pH ¼ 5; Fig.…”
Section: Effect Of Charge Carriers On the Electrochemical Responsementioning
confidence: 99%
See 1 more Smart Citation
“…[66] Such increased practical capacity depends on not only the high electronic conductivity supplied by interconnected CNTs network, but also the improvement of doping level by GO.In addition, the concentration of electrolytes plays an important role in their ionic conductivity.A td ifferent electrolyte concentrations,the specific capacities of Zn/organic batteries would be varied. [73]…”
Section: Strategies For High Specific Capacitymentioning
confidence: 99%
“…However, it was found that the discharge products of monovalent metal cations (for example, C‐O‐Li + ) were easily oxidized by the dissolved O 2 in the aqueous electrolyte, leading to the problem of self‐discharge . Subsequently, it was demonstrated that the discharge products of divalent metal cations generally exhibit improved stability and higher capacity, which is promising for the development of organic batteries using divalent charge carriers (Mg 2+ , Zn 2+ , and Ca 2+ ) . Furthermore, Compared to monovalent ions, reduced storage of divalent ions in host materials is needed to exert an equal capacity, which leads to a lower volume change of organic materials.…”
Section: Introductionmentioning
confidence: 99%